Analysis of the Student Dropout Rate at the Faculty of Electrical and Computer Engineering of the University of Prishtina, Kosovo, From 2001 to 2015 - Qamil Kabashi; Isak Shabani; Nebi Caka (IEEE Access, 2022)
This study analyzed the student dropout rate at the Faculty of Electrical and Computer Engineering (FECE) of the University of Pristina, Kosovo, from 2001 to 2015. This phenomenon is a concern for many countries, not only for students due to its emotional effects and further consequences for their university careers but also for institutions and society in general due to its broader negative impact on their authority. Over the past two decades, a significant number of students have been enrolled in these programs. However, we identified several factors that influenced young people to abandon their studies. The high dropout rate associated with FECE programs results in a lack of professionals in these areas and negatively affects the country’s economy. The main reasons given by students for such dropout were unrelated to whether students were from urban or rural areas or economic factors but were strongly related to high school programs and, to a somewhat lesser degree, to poor academic performance in certain courses. This research suggests opportunities for reducing dropout rates, as improvement in this context can be achieved by updating curricula, employing contemporary literature, applying modern teaching methodologies, improving laboratories, and reforming the behavior of certain professors. The main purpose of this study is to find a compromise between the large number of students enrolled in FECE and dropout rates; however, the findings highlight a phenomenon that is very complex and multidimensional, especially when dropout occurs after the first year of study.